2017
DOI: 10.1590/1678-4162-9710
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SNP c.-22G>A in the melanophilin gene from a dog with color dilution alopecia: case report

Abstract: RESUMOAlopecia por diluição da cor é um defeito ectodérmico caracterizado por alopecia parcial, pelagem seca e sem brilho, escamação e pápulas em áreas com defeitos na melanização e na estrutura cortical dos pelos. Os animais acometidos têm grânulos de melanina grandes e com formato irregular nos ceratinócitos basais, nas células da matriz dos pelos e nas hastes pilosas. Não existe tratamento específico que altere a evolução da síndrome, mas, em alguns animais, podem ser benéficos banhos semanais com xampu de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
3
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 7 publications
3
3
0
4
Order By: Relevance
“…Welle et al (2009) found a demonstrable association of c.-22G>A polymorphism in the MLPH gene with diluted hair colour in more than 900 dogs supporting the hypothesis that this polymorphism is indeed the cause of mutation. AlsoSantos et al (2017) in their study pointed that a mutation G>A at 5'-UTR region of exon 1 of the MLPH gene is responsible for the coat colour dilution phenotype in dogs.In total of 56 tested dogs, 50 dogs had the dominant homozygous genotype DD. Dogs with this genotype are not carriers of the diluted "Blue" colour nor are they transmitted to the offspring.…”
mentioning
confidence: 99%
“…Welle et al (2009) found a demonstrable association of c.-22G>A polymorphism in the MLPH gene with diluted hair colour in more than 900 dogs supporting the hypothesis that this polymorphism is indeed the cause of mutation. AlsoSantos et al (2017) in their study pointed that a mutation G>A at 5'-UTR region of exon 1 of the MLPH gene is responsible for the coat colour dilution phenotype in dogs.In total of 56 tested dogs, 50 dogs had the dominant homozygous genotype DD. Dogs with this genotype are not carriers of the diluted "Blue" colour nor are they transmitted to the offspring.…”
mentioning
confidence: 99%
“…Atualmente, sabe-se apenas que a origem da alopecia por diluição é relacionada à ocorrência de mutações no gene MLPH (Perego, et al, 2009). As proteínas codificadas pelo MLPH, assim como por MYO5A e RAB27A são de suma importância na pigmentação granular, atuando na distribuição, transporte e translocação de pigmentos (Santos, et al, 2017).…”
Section: Discussionunclassified
“…Indicando que animais de coloração diluída, tais como a azul, são mais predispostos à ocorrência de alopecia por diluição da cor. Não foram encontrados testes genéticos comerciais para o diagnóstico definitivo da ADC, como acreditasse que o fator genético é para a doença (Perego, et al, 2009;Santos, et al, 2017;Gouveia, et al, 2020) é de extrema importância no plano de criação, a retirada da reprodução de portadores da doença e a realização de acasalamentos que evitem o nascimento de cães diluídos, até que o completo mecanismo da doença esteja esclarecido.…”
Section: Discussionunclassified
See 2 more Smart Citations